FIGURE 5. A–D in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean ... - In, First Published (Zenodo, 2022)
FIGURE 5. A–D, Dromia erythropus (Edwards in Catesby, 1771). A, B, Male, cl 16 mm, cw 18 mm (MZUSP 40358), habitus dorsal and ventral views, respectively. C, Megalopa, cl 5 mm, cw 4.5 mm, habitus dorsal view (MZUSP 40354). D, Male, cl 21 mm, cw 23.5 mm (MZUSP 33349). Scales: A, B, 10 mm. C, 2.5 mm. Photographs by A. Pol. ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on page 14, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...